1998
DOI: 10.1046/j.1464-410x.1998.00534.x
|View full text |Cite
|
Sign up to set email alerts
|

Modified ureterosigmoidostomy (Mainz II) — technique and early results

Abstract: Modified ureterosigmoidostomy is a safe method of urinary diversion after cystectomy. A longer follow-up is needed to judge its place compared with other forms of diversion. It has a limited place in the management of incontinence in those with a longstanding conventional ureterosigmoidostomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
1
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 15 publications
3
9
1
1
Order By: Relevance
“…In comparison with other series [5,9,12] there was no serious acidosis in the present study, while others reported a need for alkalinizing agents in 51-65% of patients [4,9,10,12]. Pajor and Keleman [23] reported a need for oral medication in all their patients.…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…In comparison with other series [5,9,12] there was no serious acidosis in the present study, while others reported a need for alkalinizing agents in 51-65% of patients [4,9,10,12]. Pajor and Keleman [23] reported a need for oral medication in all their patients.…”
Section: Discussioncontrasting
confidence: 43%
“…The lesser need for bicarbonate might be attributable to preoperative renal function and patient selection. Two smaller series with 29 patients together [5,11] reported no need for oral agents.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Patients' satisfaction with this type of urinary diversion is usually high [14]. Independence from appliances such as external collecting devices and catheters favour this type of diversion from the patients' view.…”
Section: Discussionmentioning
confidence: 99%
“…Their mean (range) age at primary conduit diversion was 5.5 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) years, the mean interval between conduit diversion and conversion into continent anal diversion 8 (4-18) years and the mean age at conversion into a Mainz pouch II was 13 (8-32) years. The characteristics of the patients are summarized in Table 1.…”
Section: Methodsmentioning
confidence: 99%